Effect of Alloying Additives and Microadditives on Hardenability Increase Caused by Action of Boron - Beata Białobrzeska (Metals, 2021)
The presented work was aimed at evaluating influence of boron on hardenability of steel quantitatively and evaluating this effect during complex use of boron with other alloying additives like chromium, vanadium and titanium. For this purpose, eight melts with variable chemical compositions were prepared. From the ingots, cylindrical specimens with normalized dimensions according to EN ISO 642:1999 were cut out and subjected to full annealing at 1200 °C and to normalizing at 900 °C. Such specimens were subjected to the hardenability Jominy test. In order to distinguish the influence of boron on hardenability of a given melt and thus to eliminate the differences resulting from its chemical composition, grain size and austenitizing temperature, the obtained ideal critical diameter was corrected and the boron effectiveness factor was determined. The performed examinations and analyses showed that inadequate quantities of microadditives result in losing the benefits coming from introduction of boron as the hardenability-improving element and can even result in a reduction of hardenability of the boron-containing steel.